Optimization of Propolis and Vegetable Oils-based Soap Formulation to Enhance Product Quality and Antioxidant Properties - Rahadatul 'Aisy; Efri Mardawati; Desy Nurliasari; Hana Nur Fitriana; Awaly Ilham Dewantoro; Desy Nurliasari (Universitas Padjadjaran (Unpad), 2022)
Consumers demanded the quality of solid soap for the bath were having a solid texture, high foam stability, and fulfillment of the national quality standard in SNI 3522:2021. Soap characteristics and quality are affected by soap bases and the existence of natural additive matter with antioxidant properties such as propolis extracts. The study aims to determine an optimum formula for soap production using Response Surface Methodology (RSM) with Box-Behnken experimental design. The research conducted in several stages, its consist to propolis extraction, soap formulation and production, RSM analysis towards predetermined responses, model validation, and products characterization (in optimum formulation). Optimized factors consist of the content of propolis extracts, coconut oils, palm oils, and olive oils, while the response was moisture content, foam stability, and antioxidant inhibition. The results showed each response has a significant model to get an optimum formula for propolis extracts soap production. The optimum formula for soap production requires 1.545 g propolis extracts, 13.097 g coconut oils, 29.629 g palm oils, and 29.809 g olive oils with the model validation for each response were 95.5% moisture content, 96.5% foam stability, and 97.5% antioxidant inhibition. Soap characterization in the optimum formula fulfilled the quality standard requirement in SNI 3522:2021 its consists of 20.24% moisture content, 2.22% insoluble ingredients in ethanol, and 0.07% free alkali content. Keywords: Box-Behnken Design, Formula Optimization, Propolis Extracts, RSM, Solid Soap.